Pre-service mathematics teachers’ competencies in designing mathematical modeling tasks - Hwang, Seonyoung; Han, Sunyoung (Journal of Mathematics Teacher Education, 2025)
This study aimed to observe the competencies of pre-service mathematics teachers in designing mathematical modeling tasks. The participants were 45 pre-service mathematics teachers enrolled in a Mathematics Education Theory course at a university in Seoul, South Korea. Data were collected from surveys and task development reports. The participants submitted 19-items surveys on their prior experience and the theoretical components of competencies in mathematical modeling, along with a task development report in which they designed mathematical modeling tasks and reflected on them. After developing the criteria for appropriate mathematical modeling tasks, we evaluated and analyzed the collected data using a mixed research method. The results indicated that pre-service teachers had difficulty satisfying reality and openness, which are characteristics required for appropriate mathematical modeling tasks. The pre-service teacher group with extensive experience and a high theoretical component of competencies did not demonstrate a better grasp of real-world characteristics than the group with limited experience and a low theoretical component of competencies, indicating a disparity between the theoretical and practical components of competencies. However, the theoretical and practical components of competencies are aligned in terms of complexity. Based on these findings, we propose a direction for pre-service mathematics teacher education aimed at enhancing both the theoretical and practical components of competencies in designing mathematical modeling tasks.